Community E-content management system - Ong, Andrew Tan Hui (2020)
Not everyone in this world know how the inside of a website operates. An IT personal may know that coding language means paragraph and that can be used to insert a paragraph of content to display in the website. This in the IT world is called hardcode, whereby content is manually typed into the website and wont dynamically change in the website unless one change it from the website. But what if a user can dynamically change the content without having to know how to code? This is what we are trying to achieve currently, a dynamic community e-content management system where a user can easily manipulate data to design or to add new content into the website. The system will include four different roles of users which includes Admins, Staffs, Moderator and normal user. Each role has different access to pages except admins who has access to all pages. This system will few features such as article posting where an admin or staff can submit and article for approval which moderator can access worklists to approve or decline the article. Approved article will then be displayed on home page for other users to view. Admin is also the only role which can edit the information of all existing user in the system including changing the role of users which may allow them to be included in special roles of moderator, staffs or admin. Admins and staffs can also create news, photo books, events and downloadable content for users to view or download. Certain places such as home will also have banners which moves every few seconds. Admin and staff can also change the banner to what they want through banner maintenance page. E-Commerce will also be integrated in this system to further enhance the system and to form a better community. With this system, a community can be formed to work together and maintain a e-content management system that is easy to learn and use for everyone.